1998
DOI: 10.1021/jf980322a
|View full text |Cite
|
Sign up to set email alerts
|

Partial Synthesis and Structural Elucidation of the Oxidative Metabolites of Lycopene Identified in Tomato Paste, Tomato Juice, and Human Serum

Abstract: Two oxidative metabolites of lycopene in tomato paste, tomato juice, and human serum have been prepared by partial synthesis from oxidation of lycopene with m-chloroperbenzoic acid (MCPBA) followed by acidic hydrolysis. Extensive 1H and 13C NMR spectroscopy studies of the purified products of these reactions have confirmed that the major oxidation products of lycopene (I) are lycopene 1,2-epoxide (II) and lycopene 5,6-epoxide (III) (tentative assignment). Several diepoxides of lycopene, namely, lycopene 1,2;5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 23 publications
7
53
0
Order By: Relevance
“…Metabolism of lycopene in humans involves epoxidation at the 5,6-position, followed by rearrangement and ring opening to yield 2,6-cyclolycopene-1,5-diols I and II whose structures have been confirmed by partial and total synthesis [36,37] (Fig. 3).…”
Section: Distribution Of Carotenoids and Their Metabolites In Humansmentioning
confidence: 95%
“…Metabolism of lycopene in humans involves epoxidation at the 5,6-position, followed by rearrangement and ring opening to yield 2,6-cyclolycopene-1,5-diols I and II whose structures have been confirmed by partial and total synthesis [36,37] (Fig. 3).…”
Section: Distribution Of Carotenoids and Their Metabolites In Humansmentioning
confidence: 95%
“…Recently, several oxidative metabolites of lutein, zeaxanthin, and lycopene have been found in humans and other mammals. Lutein undergoes oxidation to ε, ε-carotene-3,3 -dione via 3-hydoxy-β, ε-caroten-3 -one 26 29 , while lycopene is converted to cyclolycopene-5,6-diols and several apolycopeneals 29,30 . These carotenoids are found at very low levels 50 pmol/mL in human plasma 27,28,30 .…”
Section: Oxidative Metabolite Of Capsanthinmentioning
confidence: 99%
“…Lycopene-1,2-epoxide and lycopene-5,6-epoxide were identified in tomatoes and tomato products by multiple groups (Britton & Goodwin 1969, 1975; Ben-Aziz et al 1973; Kamber & Pfander 1984; Khachik et al 1992). Later, nuclear magnetic resonance (NMR) research revealed that lycopene-5,6-epoxide had been misidentified and was actually 2,6-cyclolycopene-1,5-epoxide (Khachik et al 1998b). An alcohol derivative, 2,6-cyclolycopene- 1,5-diol, was also identified in tomato products and later found to be present in human blood plasma and breast milk (Khachik et al 1992, 1997, 1998a).…”
Section: Lycopenoids: Potential Oxidative Metabolites Of Lycopenementioning
confidence: 99%
“…An alcohol derivative, 2,6-cyclolycopene- 1,5-diol, was also identified in tomato products and later found to be present in human blood plasma and breast milk (Khachik et al 1992, 1997, 1998a). These researchers hypothesized that 2,6-cyclolycopene-1,5-epoxide was converted to 2,6-cyclolycopene-1,5-diol in humans, presumably during digestion, given that none of the epoxide was identified in human samples, and the alcohol is present in small quantities in the food (Khachik et al 1998b). …”
Section: Lycopenoids: Potential Oxidative Metabolites Of Lycopenementioning
confidence: 99%